Grown-up business cycles - Benjamin Pugsley; Ayşegül Şahin (Federal Reserve Bank of New York, 2014)
We document two striking facts about U.S. firm dynamics and interpret their significance for aggregate employment dynamics. The first observation is the steady decline in the firm entry rate over the last thirty years, and the second is the gradual shift of employment from younger to older firms over the same period. Both observations hold across industries and geographies. We show that, despite these trends, firms' life-cycle dynamics and business-cycle properties have remained virtually unchanged. Consequently, the reallocation of employment toward older firms results entirely from the cumulative effect of the thirty-year decline in firm entry. This "start-up deficit" has both an immediate and a delayed (by shifting the age distribution) effect on aggregate employment dynamics. Recognizing this evolving heterogeneity is crucial for understanding shifts in aggregate behavior of employment over the business cycle. With mature firms less responsive to business cycle shocks, the cyclical component of aggregate employment growth diminishes with the increasing share of mature firms. At the same time, the trend decline in firm entry masks the diminishing cyclicality during contractions and reinforces it during expansions, which generates the appearance of jobless recoveries where aggregate employment recovers slowly relative to output.
Keywords: E32; J00; L25; L26; 330; firm dynamics; employment dynamics; business cycle; entrepreneurship